Ancient Tahitian Society - Oliver, Douglas L. (University of Hawai'i Press, 1974)
"Tahiti is far famed yet too little known." Thus wrote J. M. Orsmond in 1848, and the same assertion can be made in 1972. Thousands of pages had been published about Tahiti and its neighboring islands when Orsmond uttered his judgment, and tens of thousands have been published since that time, but a unified, comprehensive, and detailed description of the pre-European ways of life of the inhabitants of those Islands is yet to appear in print. The present work, lengthy as it is, makes no such claim to comprehensiveness; rather, it is concerned mainly with the social relations of those inhabitants, and it serves up only enough about their technology, their religion, their aesthetic expressions, and so forth to place descriptions of their social relations in context and render them more comprehensible. Volumes 1 and 2 of this work are a reconstruction of the Islanders' way of life as it was believed to have been just before it began to be transformed by European influence-a period labeled the Late Indigenous Era. Volume 3 covers events in Tahiti and Mo'orea from about 1767 to 1815-a period labeled the Early European Era.